A sour cherry orchard. An excursion through Chekhovian green spaces - Negro, Francesca (Studia Rossica Posnaniensia, 2021)
The cherry orchard marks the end of Anton Chekhov’s life, consecrating him as the author who defined the threshold of the new epoch. In this article, I construe the garden as the motif linking Chekhov’s sensitivity to the general spirit of his era, revealing his poetics to the global stage as the distinctive mark of a historical and socioeconomic shift. On this path, I will clarify how the subtle difference between sour cherries and sweet cherries becomes a symbol of Chekhov’s dramatic construction, and how his poetics are built on nuances and subtle shifts in meanings, representing the irrevocable fading of a culture. A philological reflection combined with an attentive reading of Chekhov’s letters, Stanislavsky’s memoirs and scenic sketches reveal the author’s interest in the relationship between man and nature as well as the need to read his work from a more spatial-oriented standpoint. Chekhov clearly anticipates the so-called ‘spatial turn’, approaching space not through the description of a specific landscape or dramaturgical setting, but from a phenomenological point of view, leading him to profound reflections on the relationship between physical planning and socio- political development, as later conceptualised by key social thinkers such as Henry Lefebvre and Edward Soja. Chekhov’s dramaturgical construction and symbology are the result of this awareness and endless passion for nature in all its forms.